Pretty creatures : children and fiction in the English Renaissance - Witmore, Michael (Cornell University Press, 2007)
"In Pretty Creatures, Michael Witmore examines the ways in which children, with their proverbial capacity for spontaneous imitation and their imaginative absorption, came to exemplify the virtues and powers of fiction during the English Renaissance."--Jacket